Strategic Optimization of the Specific Goods and Services Tax on Overwater Tourism Services: A SWOT–PESTEL Analysis - Agus Wahyudi; Dewi Sartika Umul; Aristo Afrianto Budiman (Jurnal Ilmiah Akuntansi, 2026)
This study identifies strategic priorities for optimizing the Specific Goods and Services Tax on food and beverage provision and overwater hospitality services in Labuan Bajo, West Manggarai Regency, Indonesia. A mixed-methods design combined questionnaire data from 100 taxpayers, tourism business operators, tourists, government officials, and academics with semi-structured interviews involving local tax authorities and taxpayers. Quantitative data were analyzed using internal and external factor evaluation, SWOT, quantitative strategic planning, and PESTEL frameworks, while interview evidence was used to interpret and validate the strategic findings. The results indicate that tax administration in this sector is constrained by unclear classifications of taxable objects, overlapping central and local authority, limited monitoring of water-based businesses, insufficient taxpayer understanding, irregular financial reporting, and the suboptimal use of digital tax systems. The strategic analysis prioritizes regulatory clarification and intergovernmental coordination, taxpayer education, stronger supervision, and the integration of online reporting with cashless transaction monitoring. These findings show that improving tax revenue from overwater tourism requires more than intensified collection; it requires coordinated regulatory, technological, and institutional reform. The study contributes to local taxation and public-sector accounting literature by developing a context-specific strategic framework for tax administration in archipelagic tourism destinations.